How do you simplify #(6a^-1c^-3)/(d^0)#?

2 Answers
Apr 18, 2016

Answer:

#= color(blue)( 6)/( a c^3)#

Explanation:

#(6a^-1c^-3) / d^0#

  • As per property #color(blue)(a^0 =1#

#(6a^-1c^-3) / d^0 = (6a^-1c^-3) / color(blue)(1#

#= 6a^-1c^-3#

  • As per property #color(blue)(a^-1 =1/a#

#= 6a^-1c^-3 = 6/ color(blue)((a ^1c^3)#

#= color(blue)( 6)/( a c^3)#

Apr 18, 2016

Answer:

#6/(1a^1c^3)#

or

#6/(ac^3)#

Explanation:

To simplify #(6a^-1c^-3)/d^0#

We need to eliminate negative exponents and simplify exponents of zero.

In order to simplify negative exponents in the numerator they can be moved to the denominator to make them positive.

#a^-1 = 1/a^1#

# c^-3 = 1/c^3#

Any value to the zero power always equals one.

#d^0 = 1#

Therefore the terms convert to

#6/(1a^1c^3)#

or

#6/(ac^3)#